1977
DOI: 10.1111/j.1745-6584.1977.tb03175.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Landfill Leachate Through Glacial Tills

Abstract: To evaluate the potential of natural clay minerals for attenuating and preventing the pollution of water resources by landfill leachates, leachate was collected by anaerobic techniques from the 15‐year old Du Page County sanitary landfill near Chicago, Illinois, and was passed through 44 laboratory columns that contained various mixtures of calcium‐saturated clays and washed quartz sand. The columns were constructed to simulate slow, saturated, anaerobic flow, and manometers were placed at five locations in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…2, 3 and 4). This feature has been observed in other studies of leachate transport through soils (Griffin et al 1976;Cartwright et al 1977) and aquifer materials (Kjeldsen & Christensen 1984;Ross 1985;Kjeldsen 1986), and is similar in form to the 'hardness halo' observed at plume fringes in leachate-contaminated aquifers (Dance & Reardon 1983;Nicholson et al 1983;Christensen et al 1994).…”
Section: Attenuation Of Nhsupporting
confidence: 84%
See 1 more Smart Citation
“…2, 3 and 4). This feature has been observed in other studies of leachate transport through soils (Griffin et al 1976;Cartwright et al 1977) and aquifer materials (Kjeldsen & Christensen 1984;Ross 1985;Kjeldsen 1986), and is similar in form to the 'hardness halo' observed at plume fringes in leachate-contaminated aquifers (Dance & Reardon 1983;Nicholson et al 1983;Christensen et al 1994).…”
Section: Attenuation Of Nhsupporting
confidence: 84%
“…The shape of BTCs, mass balances, stability of anion concentrations and existence of ion-exchanging capacity ( Table 2) all suggested that ion-exchange was the main mechanism responsible for NH 4 attenuation. This feature has been observed in other studies of leachate transport through soils (Griffin et al 1976;Cartwright et al 1977) and aquifer materials (Kjeldsen & Christensen 1984;Ross 1985;Kjeldsen 1986), and is similar in form to the 'hardness halo' observed at plume fringes in leachate-contaminated aquifers (Dance & Reardon 1983;Nicholson et al 1983;Christensen et al 1994). This resulted in the desorption of the native Ca and Mg from the host substrate, which were eluted as a pulse at the leachate front (Fig.…”
Section: Attenuation Of Nhsupporting
confidence: 82%
“…Increases in the concentration of alkaline earth metals in groundwater preceding a leachate plume have been observed in the field during monitoring of the ground-water chemistry around landfill sites. Such an increase is thought to correspond to the same mechanism responsible for the Ca elution from the columns in this study and has been termed the "hardness halo" (20).…”
Section: Resultsmentioning
confidence: 64%
“…Chromatographic effects (occasionally referred to as "snow plow" effects (Star and Parlange, 1979)) have been observed in numerous field studies. This phenomenon accounts for the "hardness halo" reported around sanitary landfill leachate plumes in early studies (Griffin and Shimp, 1975;Cartwright, et aL, 1977). These effects have also been commonly misinterpreted as the consequence of transient source strengths.…”
Section: Multicomponent Transport Predictionsmentioning
confidence: 94%